Strengthening our collective commitment to the Aotearoa Climate Change Declaration : Ecological responsibility at the WCH10 - David, Bickford; Indraneil, Das; Richard, A. Griffiths (World Congress of Herpetology, 2023)
The article discusses the Aotearoa Climate Change Declaration, made at the 9th World Congress of Herpetology, Dunedin, New Zealand, 2019, and the follow-up action on the same by the Congress.